Pathogenic bacterial taxa constitute a substantial portion of fecal microbiota in common migratory bats and birds in Europe - Poosakkannu, Anbu; Xu, Yanjie; Suominen, Kati M.; Meierhofer, Melissa B.; Sorensen, Iben H.; Madsen, Jesper J.; Plaquin, Betty; Guillemain, Matthieu; Joyeux, Emmanuel; Keiss, Oskars; Lilley, Thomas M.; Lehikoinen, Aleksi; et al. (American Society for Microbiology, 2025)
Identifying the wildlife reservoirs of bacterial pathogens, spatially and temporally, is important for assessing the threats to human and the rest of the biosphere. Our objective was to study Europe-wide characteristics of the fecal microbiota of four highly mobile migratory vertebrates, that is, one bat (Pipistrellus nathusii) and three bird species (Turdus merula, Anas platyrhynchos, Columba palumbus). The 351 sample PacBio data set of almost the entire 16S rRNA gene with 438,997 amplicon sequence variants (ASVs) assigned 3,277 bacterial species. A significant proportion of the ASVs were assigned to bacterial genera having species pathogenic to human or animals. These pathogen ASVs accounted for 45% of all the ASVs and statistically were more frequent at higher latitudes and in younger age groups. In 36 samples, more than >90% of all the PacBio reads were assigned to these pathogenic genera. We designate to individuals of these samples a new term, that is, a pathogen bloomer. The pathogen bloomers, which did not display apparent macroscopic disease symptoms, were detected in Nathusius bat (n = 8; Finland and Latvia), blackbird (n = 6; Finland, Latvia and Denmark), and wood pigeon (n = 22; Finland and France), but not in mallard. Key species-level taxonomic assignments in the pathogen bloomers were the two well-known enteropathogens (Campylobacter jejuni or Escherichia coli) and one emerging enteropathogen (Escherichia marmotae). Our data imply that the studied common migratory vertebrates may contribute to the transmission of bacterial pathogens across the European continent. IMPORTANCE The understanding of gut microbiota composition and dynamics in wild vertebrate populations, especially in highly mobile vertebrates, birds and bats, remains limited. Our study sheds light on the critical knowledge gap in how common pathogenic bacterial taxa of fecal microbiota are in migratory bats and birds in Europe. We found out that bacterial genera having species pathogenic to human or animals constituted a substantial portion of the fecal microbiota in all the studied host taxa. Most importantly, we identified asymptomatic individuals that were dysbiotic with bacterial pathogen overgrowth. These previously unknown pathogen bloomers appear as potent Europe-wide transmitters of bacterial pathogens, which cause, for example, diarrhea and bacteremia in human. Our findings may contribute to better understanding of seasonal disease hotspots and pathogen spillover risks related to migratory vertebrates.